Factors Contributing to Student Language Outcomes in a Biliteracy Setting According to Teachers' and Parents' Views. Issue 3 (1st September 2020) - Sheriff, Amina; Pittas, Evdokia
Abstract: The goal of the study reported on in this article was to determine whether the current biliteracy programme in Ghana (National Literacy Acceleration Program or NALAP) and the medium of instruction are considered as factors contributing to language and literacy learning of public school students according to teachers and parents. The target group (n = 126) consisted of 63 teachers and 63 parents in the Ashanti region of Ghana. The results drawn from self-administered questionnaires indicated that most of the respondents were positive that the biliteracy programme enhances students' literacy skills. Most teachers reported that they prefer the use of both the Ghanaian L1 and English as media of classroom interaction and instruction, whereas most parents preferred English to be used as the medium of interaction. The study contributes to understanding the factors which support biliteracy learning based on teachers' and parents' views. The study made a methodological contribution in the development of a set of questionnaires.